2002
DOI: 10.1007/s005340200035
|View full text |Cite
|
Sign up to set email alerts
|

K- ras and p53 gene mutations in noncancerous biliary lesions of patients with pancreaticobiliary maljunction

Abstract: These results suggest that noncancerous lesions of the biliary epithelium in patients with pancreaticobiliary maljunction have mutations of the K- ras gene and/or the p53 gene, which provides genetic evidence that biliary epithelium has high carcinogenic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 22 publications
0
50
2
1
Order By: Relevance
“…Prophylactic cholecystectomy is performed in many institutes, as most biliary cancers that develop in PBM patients without biliary dilatation are gallbladder cancers [38,39]. However, some surgeons propose excision of the extrahepatic bile duct together with the gallbladder for PBM patients without biliary dilatation [23], because the frequency of bile duct cancer in PBM patients without biliary dilatation is higher compared to that in the general population [2], and K-ras and/or p53 gene mutations are also reportedly seen in the bile duct of PBM patients without biliary dilatation [23,40].…”
Section: Treatment Of Pbmmentioning
confidence: 99%
“…Prophylactic cholecystectomy is performed in many institutes, as most biliary cancers that develop in PBM patients without biliary dilatation are gallbladder cancers [38,39]. However, some surgeons propose excision of the extrahepatic bile duct together with the gallbladder for PBM patients without biliary dilatation [23], because the frequency of bile duct cancer in PBM patients without biliary dilatation is higher compared to that in the general population [2], and K-ras and/or p53 gene mutations are also reportedly seen in the bile duct of PBM patients without biliary dilatation [23,40].…”
Section: Treatment Of Pbmmentioning
confidence: 99%
“…However, in PBM patients, in addition to biliary tract cancers, K-ras mutation is detected in the noncancerous epithelium of the gallbladder and bile duct. Matsubara et al reported that in PBM patients without biliary carcinoma, K-ras mutation was detected in 33 and 40 % of the gallbladder and bile duct epithelium, respectively [29]. Iwase et al reported that K-ras mutation was detected in 36 % of hyperplastic gallbladder lesions in PBM patients [30].…”
Section: Gene Mutationmentioning
confidence: 99%
“…Iwase et al [23] reported detecting Kras mutations in 36% of cases with hyperplasia. Matsubara et al [25] reported mutations in 31.6% of inflammatory epithelium, and in 47.6% with both hyperplasia and metaplasia. We detected Kras mutations in 64% of cases with hyperplasia, in 28% with metaplasia, and in 17% with dysplasia [22] .…”
Section: Gene Mutationmentioning
confidence: 99%
“…Hanada et al [27] analyzed exon 58 of p53 using PCRSSCP and reported the detection of an abnormal band on exon 7, 8 in 3 of the 6 cases (50%) of stage Ⅰ gallbladder cancer with coexisting PBM. Matsubara et al [25] detected p53 gene mutation in 34.8% of cases with an inflammatory epithelium, in 47.6% with both hyperplasia and metaplasia, and in 60% with cancer, stating that these were mainly exon 5, 6, 8. However, Nagai et al [28] reported that p53 gene mutation was not detected in cases of hyperplasia and dysplasia, but that the gene mutation was observed in 4 of 26 cases (16%) of cancer.…”
Section: Gene Mutationmentioning
confidence: 99%